The impact of library use on the academic performance and information literacy skills of undergraduate students of the De La Salle Health Sciences Institute in Dasmariñas City, Cavite - Perez, Joy M. (2016)
Academic libraries are imporatant and integral parts of the teaching, learning and research process. To enhance this role, library standards are created. One of these standards is determining the student learning outcomes. Therefore, this study sought the impact of library use on the student learning through the academic activities and academic performance indicated by General Weighted Average of undergraduate students of the De La Salle Health Sciences Institute in Dasmariñas City, Cavite.